Diabetes-Related Psychopathology And Psychotherapeutic Intervention: Unique Features, Difficulties, And Constraints (Journal of Namibian Studies : History Politics Culture, 2016)
Diabetes is a significant public health issue that burdens both the afflicted person and society as a whole. The early recognition of behavioral symptoms and the development of successful psychotherapeutic interventions are implied by the psychological approach to this illness. Cognitive dysfunctions in diabetes include a slowdown in information processing, attention, memory, and concentration. These cognitive dysfunctions can lead to psychological symptoms such as a significant decrease in motivation for therapy, compliance, and self-care skills. These patients' perceived quality of life may also be negatively impacted by limitations on their everyday activities, the dangers of the treatment itself, and their perceived incapacity to manage their illness. Depression can make matters more complicated by causing a further decline in compliance and a rise in care costs. The patient, doctor, and psychologist must work together to properly manage diabetes. Changing from passive to active coping, acquiring knowledge, keeping realistic expectations, and long-term planning are all examples of improved self-care. Doctors can show empathy more consistently, which boosts their confidence. Taking into account factors that influence compliance, such as the patient's depictions of gains and losses, group norms, and ability versus desire for control, can result in a significant improvement. Techniques like family therapy, cognitive-behavioral therapy, relaxation, hypnosis, and counseling are examples of psychotherapeutic interventions.